An Archaeological Exploration on Religious Change in Liwa, West Lampung - Rusyanti, Rusyanti; Imam Hindarto; Nurul Laili; Desril Riva Shanti; Auliana Muharini (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2024)
Mountains, hills, and highlands have long been venerated in ancient beliefs as the dwelling places of deities. West Lampung, with its sacred sites, is a prime example of such places. These sites, evidenced by numerous archaeological findings, have recorded the evolution of religious significance over time. This study aims to explore the transformation of these sacred sites and their contemporary interpretations. The main objective of this research is to explore the progression of religious shift in Liwa, West Lampung. By examining archaeological records from 2011 to 2018, this study constructs chronological narrative of the region’s early religious history. The findings reveal four prevalent patterns that encapsulate the religious transformations from the 10th to the 19th centuries. These patterns, derived from archaeological data and supplemented by contextual and historical analysis, indicate a shift in religious practices in this region. This shift aligns with Lewis Rambo’s model of religious change in a macro context, characterized by encounter, interaction, communication and subsequent consequences. This study, therefore, provides valuable insights into the dynamic nature of religious practices and beliefs in Liwa over centuries.